An economic evaluation of future electricity use in Irish data centres - Bryan Coyne; Eleanor Denny (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2018)
Data centres are a critical component of the modern, connected economy. They facilitate activities such as cloud computing, communication and data storage. In Ireland, the increasing presence and significant electricity demand of data centres is a growing concern for electricity generation and grid infrastructure. It is anticipated that future technological advances will drive efficiencies to help reduce energy demand. However, the specific technology and pattern of market adoption are currently unknown. This paper details recent developments in data centre cooling technology and applies an economic model of diffusion for the Irish data centre sector to model the adoption of a liquid cooling technology over the next decade. Results note that the pattern of market adoption for new technologies is key to modelling market changes, with consequences for national electricity consumption and the emissions associated with electricity generation. Estimates of the twelve-year reduction in national electricity demand from 2015-2026 range from 2.40% and 2.43% for New facilities only adopt (ND) and All facilities adopt (AD) scenarios, respectively.
Keywords: Q40; Q47; O330; 330; Data centres; energy; electricity consumption technology adoption; diffusion; ebergy forecasting